Pengaruh Gaya Kepemimpinan dan Kepuasan Kerja Karyawan pada Perusahaan Manufaktur di Surabaya - Yessy Auralia Febiyanti (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
In an increasingly competitive era of globalization, companies worldwide face significant challenges in improving performance and productivity to remain competitive in the global market. One important factor influencing employee performance and productivity is leadership style. This study aims to analyze the influence of leadership style on employee job satisfaction at a manufacturing company in Surabaya. The research method used a quantitative approach with primary data collected through questionnaires completed by respondents at a manufacturing company in Surabaya. The results showed that the majority of respondents were satisfied with their jobs at the manufacturing company, with a preference for democratic and transformational leadership styles. These leadership styles are considered capable of improving communication, a sense of fairness, and employee career development. Although job satisfaction was achieved, the results also revealed room for improvement, particularly in aspects of more open communication, fairness in performance appraisals, and overall company development. Therefore, companies are advised to pay attention to these aspects to improve employee satisfaction and performance.